Rancangan Aplikasi Panduan Ibadah Umroh Dengan Metode Timeline Tree - Muntahanah Muntahanah; Nanda Febrina; Yovi Apridiansyah (UNIVED Press, 2023)
Abstract_In Indonesia, the number of Android system smartphone users is 88.37% in 2017. Developments in the field of information technology are currently progressing and developing rapidly, especially in the development of mobile phones, starting from hardware such as Samsung, Lenovo, Oppo, Xiomy and other devices that embed Android. as an operating system because it has many advantages. Umrah worship is mostly carried out by Muslims in Indonesia nowadays due to the long waiting time in the queue to be able to go on pilgrimage. Guidance is given directly or indirectly. Directly, the department of religion or the Hajj Guidance Group (KBIH) conducts hands-on training on guidance for the Hajj and Umrah pilgrimages. In using a guidebook prepared by travel or smartphones that search for prayers via Google and make it a little difficult for the congregation because of the many references. This was considered impractical because the guidebook that was included with the travel party was easily scattered, got wet with water or could even be torn so that it could no longer be used. Created a system that continues the design made in this study so that it can be used by related parties.